Global expression profiling and pathway analysis of mouse mammary tumor reveals strain and stage specific dysregulated pathways in breast cancer progression. Issue 8 (18th April 2018) - Mei, Yan; Yang, Jun-Ping; Lang, Yan-Hong; Peng, Li-Xia; Yang, Ming-Ming; Liu, Qing; Meng, Dong-Fang; Zheng, Li-Sheng; Qiang, Yuan-Yuan; Xu, Liang; Li, Chang-Zhi; Wei, Wen-Wen; et al.
ABSTRACT: It is believed that the alteration of tissue microenvironment would affect cancer initiation and progression. However, little is known in terms of the underlying molecular mechanisms that would affect the initiation and progression of breast cancer. In the present study, we use two murine mammary tumor models with different speeds of tumor initiation and progression for whole genome expression profiling to reveal the involved genes and signaling pathways. The pathways regulating PI3K-Akt signaling and Ras signaling were activated in Fvb mice and promoted tumor progression. Contrastingly, the pathways regulating apoptosis and cellular senescence were activated in Fvb.B6 mice and suppressed tumor progression. We identified distinct patterns of oncogenic pathways activation at different stages of breast cancer, and uncovered five oncogenic pathways that were activated in both human and mouse breast cancers. The genes and pathways discovered in our study would be useful information for other researchers and drug development.